Designing an IT Service Management System with Naïve Bayes Method and Knowledge Base to Support IT Services - Bagus Tri Mahardika; Mochammad Fiqri Ash'ari (Publikasi Indonesia, 2024)
SMK Pelita Alam is a health school that has been using IT systems rapidly in recent years to assist with various tasks. With the increased use of IT, new problems arise in IT service management, some of which are the increased volulme of data and information that must be managed. Therefore, the purpose of this research is to create a Helpdesk Ticketing application at SMK Pelita Alam that is equipped with a classification of the urgency level of complaints, and several other features such as a Knowledge Base that provides an updated knowledge base to improve responses to common questions and an AI Chatbot to ask various kinds of questions. This research uses the Waterfall research method while the algorithm used for complaint classification is Naive Bayes Classifier. This algorithm is implemented on the create ticket form, and this application is developed web-based. The results showed that the designed system can improve IT service quality, operational efficiency, and user satisfaction. The system can also provide useful information for future IT service planning and improvement. This research is expected to make a positive contribution to the development of assistance service systems at SMK Pellita Alam...